DISCRIMINANT ANALYSIS THROUGH FISHER METHOD ON STUDENT'S MATERIALS BUILDING IN SMP 1 BANDA ACEH - Y Yuhasriati; Johan Yunus; Erni Maidiyah; Bintang Zaura (Jurnal Geuthèë: Penelitian Multidisiplin, 2019)
The study is done for determining how many students and how the percentage of students who have mastered the material geometry about prism and pyramid, and getting the discriminant function about the mastery of the material. The study population was the entire eighth grade students of SMP Kasih Banda Aceh while the sample were students of class VIII-1 and VIII-8 to 66 students. Based on the research that has been done using the fisher discriminant analysis method, 18,18% of students have mastered the material geometry and 81,82% of students have not mastered the material geometry. It means that from 66 students only 12 students were able to master the material geometry about well- prism and pyramid. The discriminant function that is formed is and .